Olive oil with high polyphenolic content induces both beneficial and harmful alterations on rat redox status depending on the tissue - Paraskevi Kouka; Fotios Tekos; Zoi Papoutsaki; Panagiotis Stathopoulos; Maria Halabalaki; Maria Tsantarliotou; Ioannis Zervos; Charitini Nepka; Jyrki Liesivuori; Valerii N. Rakitskii; Aristidis Tsatsakis; Aristidis S. Veskoukis; et al. (Elsevier, 2022)
Olive oil (OO) possesses a predominant role in the diet of Mediterranean countries. According to a health claim approved by the European Food Safety Authority, OO protects against oxidative stress‑induced lipid peroxidation in human blood, when it contains at least 5 mg of hydroxytyrosol and its derivatives per 20 g. However, studies regarding the effects of a total OO biophenols on redox status in vivo are scarce and either observational and do not provide a holistic picture of their action in tissues. Following a series of in vitro screening tests an OO containing biophenols at 800 mg/kg of OO was administered for 14 days to male Wistar rats at a dose corresponding to 20 g OO/per day to humans. Our results showed that OO reinforced the antioxidant profile of blood, brain, muscle and small intestine, it induced oxidative stress in spleen, pancreas, liver and heart, whereas no distinct effects were observed in lung, colon and kidney. The seemingly negative effects of OO follow the recently formulated idea in toxicology, namely the real life exposure scenario. This study reports that OO, although considered a nutritional source rich in antioxidants, it exerts a tissues specific action when administered in vivo.